Arabic Vocabulary: Konsep Aplikasi Berbasis Augmented Reality untuk Meningkatkan Penguasaan Kosakata Bahasa Arab - Aisyah Cahyani; Moh. Fauzan; Kurniawati Aprilia Rusdiana Putri; Ariyani Dwi Larasati; Nurrotu Halimatus Sakdiyah; Annas Tohuri (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Language is a communication tool used by everyone to express their desires. Many languages exist in the world, one of which is Arabic. In Indonesia, Arabic is one of the subjects taught at the kindergarten (TK) level with students being introduced to Arabic vocabulary as it is the key language component in order for learners to be able to use the language. However, previous studies found that learning Arabic vocabularies is very challenging for so many people. For this underlying reason, the researcher initiated a breakthrough to develop an Arabic vocabulary application to improve the vocabulary mastery. This breakthrough is in the form of an Augmented Reality-based application with its development using ADDIE method. This research was carried out in class X MAN Kota Batu with the data collection instruments including expert validation instruments and student assessments with the help of a Likert scale. In its implementation, the results were very feasible in all aspects, which included aspects of content, language, and presentation as well as in the media aspect. In this case, the same results were obtained between experts and students. It can be concluded that the development of this Arabic Vocabulary application is necessary to help optimize the learning of Arabic. Keywords: Arabic language, vocabulary, augmented reality. Abstrak: Bahasa adalah alat komunikasi yang digunakan oleh setiap orang untuk mengungkapkan keinginannya. Ada banyak bahasa yang ada di dunia, salah satunya adalah bahasa Arab. Di Indonesia, bahasa Arab merupakan salah satu pelajaran yang sudah mulai diajarkan pada tingkat Taman Kanak-kanak (TK), siswa dikenalkan mengenai kosakata bahasa Arab. Kemahiran seseorang dalam berbahasa memerlukan peran kosakata. Namun tidak jarang penulis menemui, ketika belajar bahasa Arab, banyak orang mengalami kesulitan dalam hal kosakata. Atas dasar inilah, peneliti menggagas sebuah terobosan baru dalam upaya membuat konsep aplikasi Arabic Vocabulary dan meningkatkan penguasaan kosakata bahasa Arab. Terobosan ini berupa konsep aplikasi berbasis Augmented Reality dengan metode pengembangannya adalah ADDIE. Penelitian ini dilaksanakan di kelas X MAN Kota Batu dengan instrumen pengumpulan data yang digunakan adalah instrumen validasi ahli dan penilaian peserta didik dengan bantuan skala likert. Dalam implementasinya yang dilaksanakan di kelas X MAN Kota Batu didapatkan hasil sangat layak pada semua aspek, yang meliputi aspek isi, bahasa dan penyajian begitu juga pada aspek media didapatkan hasil yang sama pula antara para ahli dan peserta didik dalam implementasi aplikasi Arabic Vocabulary yang berbasis Augmented Reality. Dapat ditarik kesimpulan bahwa kebutuhan akan aplikasi Arabic Vocabulary ini dirasa perlu ketika belajar bahasa Arab. Kata kunci: bahasa Arab, kosakata, augmented reality